PENCEGAHAN TINDAK PIDANA KORUPSI TERHADAP PENGELOLAAN DANA BANSOS COVID-19 - Adryan Putra Alamsyah; Edy Soesanto; Muhammad Fikri Al Husaini (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This research aims to find out the form of distribution of social assistance funds for communities affected by Covid-19, whether they are in accordance with the regulations for managing social assistance funds during the Covid-19 period, and to find out prevention efforts to prevent criminal acts of corruption against managers of Covid-19 social assistance funds. . This research uses normative and empirical legal research types with a social and statutory approach. Types and sources of data using primary data and secondary data. Data analysis will be analyzed and processed using qualitative methods then presented descriptively which is then combined prescriptively. The results of the research show that we can see that the form of distribution of social assistance funds for the community in the central government is that the form of distribution of social assistance funds is divided into two, namely there is cash social assistance and there is social assistance for basic necessities, whereas if we look at regional governments the form of distribution of social assistance funds is only in cash, such as aid. MSMEs (Micro, Small and Medium Enterprises) and sub-district BLT (Direct Cash Assistance) assistance. The regulations for managing social assistance funds during the Covid-19 period are appropriate because we refer to the Minister of Social Affairs' Decree No. 54/HUK/2020 concerning the implementation of basic food social assistance and cash social assistance in handling the impact of the 2019 corona virus disease (Covid-19). Efforts to prevent criminal acts of corruption from occurring in the management of Covid-19 social assistance funds are by supervising planning, implementation and utilization. Supervision is an effort to ensure that something is carried out in accordance with established regulations.